Load Balancing Evaluation Tools for a Private Cloud: A Comparative Study - Saeid, Sahand Kh.; Ali Yahiya, Tara (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2018)
Cloud computing turns out to be an emerging technology that revolutionized the world of IT infrastructure. However, since the number of users is increasing daily, the demand for cloud services is increasing too. Thus, congestion occurs on the servers that provide services in the cloud. To avoid congestion, we used load balancer tools such as HAProxy and Nginx to intercept the requests of users and distribute them evenly to the servers. Jmeter is used to measure the performance metrics of least connection algorithm in terms of CPU utilization, response time, and concurrency level. Results showed high performance of HAProxy compared to Nginx in terms of response time and treating requests. Furthermore, we examined the characteristic of availability of the load balancer through deploying redundant load balancers, and we studied the effect of the failure of the load balancer on the quality of service of the end users. Keepalived is used to ensure a smooth transition between the two load balancers. According to the concurrency level, results proved that the number of unsuccessful requests during the failure of the master load balancer is proportionally minuscule compared to the total number of requests sent in a normal situation.